The Effect of National Culture on Knowledge Sharing: Empirical Study on University Students in UK - Hussien, Safaa; Khedr, Wessam (The Arab Journal of Administration, 2021)
This paper explores the effect of national culture on knowledge sharing attitude among an international sample of students in UK universities. Following Hofstede’s cultural instrument, hypothesis was examined to detect if students from different culture groups will have different knowledge sharing attitude. Moreover, different motivators and barriers to knowledge sharing were examined to see if participants from different cultural backgrounds would perceive different types of motivators and barriers. Data were collected from 103 students using online questionnaire. After confirming the validity and reliability of the measures, descriptive analysis showed that the majority of the sample has a high knowledge sharing attitude, moreover, T-test showed no significant differences in knowledge sharing attitudes between participants from different cultural backgrounds. However, there was a significant difference on some motivators and barriers, detected between students from different cultures This paper tried to explore the role of culture in knowledge sharing among a sample of international students. The study not only adds to the few number of research that explored the role of culture on knowledge sharing, but it also adds to the literature of KS within students’ context, thus flagging some important findings that could be of interest to higher education institutes in UK and other multicultural universities worldwide.